2011
DOI: 10.1007/s00240-011-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral very large calcium oxalate stones in the seminal vesicles: case report and literature review

Abstract: A 29-year-old man with hypospadias and bilateral undescended testicles presented with recurrent attacks of lower urinary tract infections and painful ejaculation. He was diagnosed to have very large bilateral seminal vesicle stones. The pelvis X-ray showed two radio-densities located in the pelvis with symmetrical appearance while Ultrasound showed them as echogenic structures with posterior acoustic shadowing. In magnetic resonance imaging (MRI) of the pelvis they appeared hypointense in both T1-weighted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…Patients with SVC also complained of lower abdominal pain, perineal discomfort or pain, and/or infertility (Miao et al, 2020; Li, 1991). Some patients with large SVC presented with a history of passing increasingly painful 'grit' in their ejaculate, and others complained of recurrent lower urinary tract infections (Williams, Christodoulidou, & Nigam, 2017; Hadidi, Hadidy, Alrabadi, Ahdul‐Wahab, & Murshidi, 2011). Differential diagnoses included posterior urethral haemangioma (Han, Zhou, Fan, Tian, & Zhang 2015; Tian et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SVC also complained of lower abdominal pain, perineal discomfort or pain, and/or infertility (Miao et al, 2020; Li, 1991). Some patients with large SVC presented with a history of passing increasingly painful 'grit' in their ejaculate, and others complained of recurrent lower urinary tract infections (Williams, Christodoulidou, & Nigam, 2017; Hadidi, Hadidy, Alrabadi, Ahdul‐Wahab, & Murshidi, 2011). Differential diagnoses included posterior urethral haemangioma (Han, Zhou, Fan, Tian, & Zhang 2015; Tian et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The literature review on SVC from 1983 to date revealed a case of SVC reported in 1983 and, thereafter, most of the studies contained a single patient or small number of cases without reporting SVC features or aetiological analysis. SVC can be solitary or multiple and occur in different sizes . In the present study, we identified several cases with multiple SVC, most of which were yellow or yellow/brown with irregular shapes.…”
Section: Discussionmentioning
confidence: 74%
“…As shown in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]), whilst the remaining six were original research articles [21][22][23][24][25][26]. Amongst all the articles included, only seven studies or cases analysed the composition of SVC with small case numbers.…”
Section: Literature Searchmentioning
confidence: 99%
“…Se ha encontrado que la incidencia aumenta en pacientes mayores de 40 años y con comorbilidades tales como diabetes mellitus, prostatitis crónica, tuberculosis genitourinaria, esquistosomiasis, criptorquidia e hipospadias. [3][4][5] Su etiología y fisiopatología son inciertas, se han postulado una serie de teorías, las cuales plantean que la formación de los cálculos es generada por la alteración en el microambiente propio de las vesículas seminales. Dentro de ellas se producen sustancias como fructosa, proteínas, prostaglandinas, así como sustancias mucoides cubiertas por sales como: fosfato de calcio, carbonato, urato, fosfato y estruvita.…”
Section: Discussionunclassified